2015
DOI: 10.1179/1743284714y.0000000676
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and tensile properties of as extruded and as aged Mg–Al–Zn–Mn–Sn alloy

Abstract: The effect of 0–4 wt- Sn addition on the microstructure and tensile properties of AZ80 alloys was investigated. The results indicated that Mg2Sn particles were barely formed during the extrusion process until the content of Sn is >2 wt-. The dislocation density in alloys after extrusion declined with the addition of Sn due to the promotion of dynamic recrystallisation after adding Sn. In aging treatment, Mg17Al12 precipitates were promoted by Sn and the phases distributed uniformly at low density level of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In previous study, the main phases in this alloy were Mg 17 Al 12 phase and Mg 2 Sn phase [20] which were measured by XRD and consistent with others' related researches. It showed that in this alloy Mg 2 Sn suppressed precipitation of DP-Mg 17 Al 12 phases and Sn promoted CP-Mg 17 Al 12 phases.…”
Section: Introductionmentioning
confidence: 53%
“…In previous study, the main phases in this alloy were Mg 17 Al 12 phase and Mg 2 Sn phase [20] which were measured by XRD and consistent with others' related researches. It showed that in this alloy Mg 2 Sn suppressed precipitation of DP-Mg 17 Al 12 phases and Sn promoted CP-Mg 17 Al 12 phases.…”
Section: Introductionmentioning
confidence: 53%
“…It can be seen that the HPRed ATZ821À1.0Y alloy exhibits impressive mechanical properties with a YS of %248 MPa, a UTS of %385 MPa, and a UE of %19.6%. Compared with extruded and rolled Mg-Al-Sn-Znbased alloys reported in literature (Figure 10a), [11][12][13][14][28][29][30][31] the present as-extruded and HPRed ATZ821À1.0Y alloys exhibit a much higher ductility and comparable UTS. The main reason for the much higher ductility of as-extruded ATZ821À1.0Y alloy in the present work is the enhancement of <c þ a> slips due to the solid solution of Y atoms and the weak texture.…”
Section: Mechanical Propertiesmentioning
confidence: 88%
“…Recent studies have indicated that the addition of Sn can greatly enhance the strength (e.g., ultimate tensile strength [UTS] > 340 MPa) of wrought Mg-Al-Zn alloys containing a high amount of Al, without significant influence on the ductility (e.g., elongation to failure of 7-18%). [11][12][13][14] Furthermore, the combined addition of rare earth (RE) (Y, Nd, Ce, etc.) elements and non-RE elements (Sn, Zn, Ca, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Rapid solidification (RS) generally obtains fine microstructure, supersaturated solid solution and nonequilibrium phases, which can vastly improve the mechanical properties of Mg alloys [11][12][13][14][15]. Common rapid solidification techniques include gas atomisation (GA), ultrasonic atomisation (UA), planar flow casting (PFC) and melt-spinning (MS) techniques [16]. Thermal deformation processing is also an effective approach to fine grains by dynamic recrystallisation (DRX), and it is usually applied to Mg-Al, Mg-Zn and Mg-Sn alloy systems [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Common rapid solidification techniques include gas atomisation (GA), ultrasonic atomisation (UA), planar flow casting (PFC) and melt-spinning (MS) techniques [16]. Thermal deformation processing is also an effective approach to fine grains by dynamic recrystallisation (DRX), and it is usually applied to Mg-Al, Mg-Zn and Mg-Sn alloy systems [16][17][18]. Kawamura et al [19] have prepared the Mg 97 Zn 1 Y 2 alloy with excellent yield strength above 600 MPa by the melt-spinning technique and hot extrusion.…”
Section: Introductionmentioning
confidence: 99%